INCREASING THE EFFICIENCY OF PROJECT-BASED LEARNING DURING MATHEMATICS TEACHING AT SCHOOL - Nurbavliyev, O.K.; Sydykhov, B.D. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
Project-Based Learning (PBL) is an educational approach that emphasizes the development of learners’ critical thinking, problem-solving, collaboration, and communication skills through the completion of a project that integrates various academic subjects. PBL involves learners in a hands-on, experiential learning process, where they work collaboratively to investigate a complex question or problem, and create a product or solution that demonstrates their learning. PBL encourages learners to take ownership of their learning by engaging them in the project planning, research, and presentation processes. PBL has been found to improve learners’ academic achievement, as well as their motivation and engagement in learning. PBL is a valuable educational approach that can prepare learners for success in the 21st century workplace by developing skills that are highly valued by employers, such as critical thinking, problem-solving, creativity, and collaboration.